Noncollinear ferrimagnetism and anomalous Hall effects in Mn4N thin films - Venkatesan, Munuswamy; Coey, John (My University, 2022)
Thin films of Mn 4 N and related ternary metallic perovskites with perpendicular anisotropy are interesting for spintronics, but their magnetic structures differ from the triangular ferrimagnetism of the bulk. A temperature-independent anomalous Hall conductivity of − 90 Ω – 1 c m – 1 was found in Mn 4 N films, in addition to the normal temperature-dependent contribution. Based on known spin structures of bulk Mn 3 Z N compounds and the distance dependence of the Mn-Mn exchange for first- and second-neighbor Mn-Mn pairs, we propose a topological noncollinear spin structure for the Mn 4 N films with perpendicular anisotropy. The Letter shows how a small change in symmetry of the spin structure can influence the magnetotransport properties of frustrated ferrimagnetic films.
PUBLISHED
Keywords: Anomalous Hall effect; Hall effect; Magnetic interactions; Magnetism; Magnetotransport; Nanoscience & Materials; Applied physics; Condensed matter, electronic, magnetic and superconductive properties; Magnetism and spin electronics; Nanotechnology; Physics